European anti-Catholicism in a comparative and transnational perspective - Werner, Yvonne Maria; Harvard, Jonas (Amsterdam : Editions Rodopi, 2013)
Tales about treacherous Jesuits and scheming popes are an important and pervasive part of European culture. They belong to a set of ideas, images, and practices that, when grouped under the label anti-Catholicism, represent a phenomenon that can be traced back to the Reformation. Anti-Catholic movements and sentiments crossed boundaries between European countries, contributing to the early modern consolidation of national identities. In the nineteenth century, secularist movements adopted and transformed confessional criticism in a new internationalist dimension that was articulated across the.
The Jesuit Stereotype -- An Image of the Universal Enemy in Finnish NationalismNorway and the Jesuit Order: A History of Anti-Catholicism; Catholicism and the Idea of Public Legitimacy in Sweden; Scottish Anti-Catholicism in a British and European Context: The 'North Pole Mission' and Victorian Scotland
Description based upon print version of record.
Description based on print version record.
Keywords: Anti-Catholicism -- Europe -- History; Christianity -- Europe -- History; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Electronic books; Electronic books